2009
DOI: 10.1590/s0100-40422009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Extração seletiva de metais pesados em sedimentos de fundo do Rio Tietê, São Paulo

Abstract: Recebido em 24/10/07; aceito em 13/8/08; publicado na web em 20/1/09 SELECTIVE EXTRACTION OF HEAVY METALS IN BOTTOM SEDIMENTS FROM TIETÊ RIVER, SÃO PAULO. Sediment samples from Tietê river were submitted to chemical and sequential extractions of heavy metals (Cd, Cr, Cu, Ni, Pb and Zn). It was followed a single extraction by using 0.1 mol L -1 hydrochloric acid and a sequential procedure to evaluate possible chemical associations described as exchangeable, carbonate, reducible oxides, sulfide, organic matter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 18 publications
(32 reference statements)
2
8
0
16
Order By: Relevance
“…After station 7 (Barra Bonita), the increase of Cu, Cr and Ni concentrations coincides with the anthropogenic influences from agriculture to urban areas. Bevilacqua et al (2009) at the middle part of the Tietê River basin observed a similar pattern. The case of Cu seems to be more serious, as it is used to control algae in hydroelectric reservoirs.…”
Section: Heavy Metal Content and Downstream Distribution Patternssupporting
confidence: 63%
“…After station 7 (Barra Bonita), the increase of Cu, Cr and Ni concentrations coincides with the anthropogenic influences from agriculture to urban areas. Bevilacqua et al (2009) at the middle part of the Tietê River basin observed a similar pattern. The case of Cu seems to be more serious, as it is used to control algae in hydroelectric reservoirs.…”
Section: Heavy Metal Content and Downstream Distribution Patternssupporting
confidence: 63%
“…To evaluate the potentially mobile metals, cold acid extraction procedures were used, in order to simulate the natural mobilization processes of these more "labile" elements of the sediments (Bevilacqua et al 2009). The extraction procedure with 0.5mol/L diluted hydrochloric acid (HCl) was applied (Sutherland and Tack 2008, Bevilacqua et al 2009, Li et al 2009). The procedure is based on the extraction of 0.5 g of sample with 10 mL of a solution of 0.5 mol/L HCl under continuous stirring at 200 rpm for 1 h at 20°C.…”
Section: Methodsmentioning
confidence: 99%
“…As extrações foram baseadas nos trabalhos de Usero e colaboradores 25 e Bevilacqua e colaboradores. 26 Foi utilizado aproximadamente 1 g de sedimento, transferido para o tubo tipo Falcon (capacidade de 15 mL) e adicionado 10 mL de solução de extração (solução tampão de ácido acético/acetato de sódio a 0,1 mol L -1 ; pH 5,0). As amostras foram colocadas no agitador rotatório de frascos (agitação vertical, 30 ± 2 rotações por minuto), pelo período de 4 horas.…”
Section: Avaliação Da Biodisponibilidade De Nutrientes Metais Alcaliunclassified